Model of Working Capital Financing of Mekaar Pruducts in Sme‘s Empowerment Framework at PT. Permodalan Nasional Madani in Surabaya - Nurul Fatmawati (NAROTAMA UNIVERSITY, Indonesia, 2019)
The purpose of this study was to determine the role of microfinance / non-bank institutions in the pre-prosperous female SME empowerment program at PT. Permodalan Nasional Madani in Surabaya. This research method uses a qualitative descriptive approach, the data used in this study are primary data with internal and external data sources. This research was conducted by conducting surveys, interviews, documentation, and questionnaires on 12 respondents from a total of 30 respondents who were still active as customers at PNM Mekaar Surabaya. The results and findings of this study reveal that the joint system of working capital financing is very effective for SMEs, especially for financial institutions whose targets are pre-prosperous women. This is reflected in the average score of perceptions for 15 statements of 75.8%, while each statement has a score of 62.3%, therefore the reconstruction of the financing model is said to be good.